The Relationship Between the Recovery of Balance and Cognitive Functions During Physiotherapy in Patients with Traumatic Brain Injury - E. Lendraitienė; U. Buraitytė; D. Petruševičienė; L. Varžaitytė (Neurologijos seminarai)
Background. There is growing evidence that cognitive and motor functions after traumatic brain injury (TBI) are actually related. However, we failed to find any concrete evidence proving the interrelationship between balance and cognitive functions therefore the effects of TBI on cognitive and motor functions remain not fully evaluated. Objective. The aim of the study was to evaluate the relationship between the recovery of balance and cognitive functions during physiotherapy in patients with TBI. The Methods of the study. The study included 25 individuals who had sustained TBI. The subjects were distributed into two groups: Group 1 consisted of 15 subjects with moderate TBI, and Group 2 – of 10 subjects with severe TBI. The cognitive functions were evaluated using the Mini Mental State Examination, the level of cognitive functioning (consciousness) was evaluated using the Rancho Los Amigos scale, and balance was assessed with the help of the Fullerton Advanced Balance Scale. Results and conclusions. After physiotherapy, improvement was observed in the balance of subjects with moderate and severe TBI. Physiotherapy improved cognitive functions in subjects with moderate and severe TBI. The search for correlations between individual items on the Fullerton Advanced Balance Scale and Mini Mental State Examination revealed relationship between some items in both groups.